Fluticasone at different doses for chronic asthma in adults and children - Adams, Nick P (Cochrane Database Syst Rev, 2008)
BACKGROUND: Inhaled fluticasone propionate (FP) is a high‐potency inhaled corticosteroid used in the treatment of asthma. OBJECTIVES: 1. To assess the efficacy and safety outcomes of inhaled fluticasone at different nominal daily doses in the treatment of chronic asthma.   2. To test for the presence of a dose‐response effect. SEARCH METHODS: We searched the Cochrane Airways Group Trials Register (January 2008). SELECTION CRITERIA: Randomised trials in children and adults comparing fluticasone at different nominal daily doses in the treatment of chronic asthma. Two reviewers independently assessed articles for inclusion and methodological quality. DATA COLLECTION AND ANALYSIS: One review author extracted data. These were checked and verified by a second reviewer. Quantitative analyses where undertaken using Review Manager. MAIN RESULTS: Fifty‐one published and unpublished trials (representing 55 group comparisons, 10,797 participants) met the inclusion criteria. In asthmatics with mild to moderate disease who were not on oral steroids, FP did not exhibit a dose‐response effect in the lower dose comparisons in FEV1 (50mcg, 100mcg, 200mcg and 4‐500mcg daily). There were no statistically significant differences between 4‐500mcg and 800‐1000mcg, and between 50‐100 and 800‐1000mcg of FP. When 200mcg was compared with 800‐1000mcg daily FEV1 favoured the four/five fold increase. For PEF, a dose response was present with FP when low and moderate, and low and high doses of FP were compared. There was no evidence of a dose‐response effect on symptoms or rescue beta‐2 agonist use. The likelihood of hoarseness and oral candidiasis was significantly greater for the higher doses (800 to 1000 µg/day). People with oral steroid‐dependent asthma treated with FP (2000 µg/day) were significantly more likely to reduce oral prednisolone than those on 1000 to 1500 µg/day (Peto odds Ratio 2.8, 95% CI 1.3 to 6.3). The highest dose also allowed a significant reduction in daily oral prednisolone dose compared to 1000 to 1500 µg/day (WMD 2.0 mg/day, 95% CI 0.1 to 4.0 mg/day). AUTHORS' CONCLUSIONS: We have not found evidence of a pronounced dose response in FEV1 with increasing doses of fluticasone. The number of studies contributing to our primary outcomes was low. At dose ratios of 1:2, there are statistically significant differences in favour of the higher dose in morning peak flow across the low dose range. The clinical impact of these differences is open to interpretation. Patients with moderate disease achieve similar levels of asthma control on medium doses of fluticasone (400 to 500 µg/day) as they do on high doses (800 to 1000 µg/day). More work in severe asthma would help to confirm that doses of FP above 500 µg/day confer greater benefit in this subgroup than doses of around 200 µg/day. In oral corticosteroid‐dependent asthmatics, reductions in prednisolone requirement may be gained with FP 2000 µg/day.